Шаперони HSP90 як стабілізатор росту і формотворення рослин: мікроеволюційний аспект - Козеко, Л.Є. (Фактори експериментальної еволюції організмів, 2016)
Aim. Chaperones HSP90 have been considered as a mechanism for buffering and accumulating genetic changes which
could be important for developmental networks. An analysis of polymorphic Arabidopsis thaliana seeds was carried out
to test this hypothesis. Methods. Seeds from a natural population as well as Col seeds irradiated with UV-B and gammarays and non-irradiated (control) were treated with an inhibitor of HSP90 geldanamycin (GDA). Seed germinability
and seedling growth rates and morphological variation were analyzed. Results. GDA enhanced the growth rate and
morphological diversity in polymorphic material and, at the same time, eliminated a part of the weaker organisms.
Conclusions. The role of HSP90 in the concealment and release of genetic polymorphism, support of homeostasis and
stabilization («canalization») of plant growth and morphogenesis may be an important mechanism for morphological
evolution.
Keywords: heat shock protein 90, Arabidopsis thaliana, polymorphism, phenotype, morphological evolution.